Technology for decreasing active drag at maximal swimming velocity - Kolmogorov, S.; Lyapin, S.; Rumyantseva, O.; Vilas-Boas, J. P. (coachesinfo.com, 2000)
The article describes the technology for decreasing active drag at the maximal swimming velocity. This technology can be used for both elite and sub-elite swimmers of different sex, age and qualification. It has been developed on the basis of optimal interaction between two functional systems of a swimmer (biomechanical and metabolic). The technology includes three components (training exercises; choice of training categories according to their international classification; use of special technical devices), as well as a set of concrete methods and technical procedures. The parameters, necessary for the research, have been measured by the method of small perturbations with the help of an additional hydrodynamic body.